PENENTUAN KADAR TOTAL FENOLIK, FLAVONOID, DAN KAROTENOID EKSTRAK METANOL KLIKA ANAK DARA (Croton oblongus Burm.f.) - Haeria Haeria; Surya Ningsi; Adilah Daeng Riaji (Jurnal Farmasi UIN Alauddin Makassar, 2014)
A study concerning the determination level total of phenolic, flavonoid, and carotenoid of methanol extract anak dara’s cortex (Croton oblongus Burm.f.). Anak dara (Croton oblongus Burm.f.) is native to Indonesia, which is known have antioxidant activity. The purpose of this study was to determine the levels total phenolics, flavonoids, and carotenoids  methanol extract in cortex anak dara (Croton oblongus Burm.f.). Extraction of chemical constituents of anak dara (Croton oblongus Burm.f.) performed by maceration method using methanol until the filtrate was clear. Total phenolic content was tested using standard gallic acid, total flavonoid quercetin was tested using a standard, and total carotenoid content was tested using standard β-carotene To determine the total concentration of compounds in the methanol extract of cortex anak dara (Croton oblongus Burm.f.), compound analysis is carried out using Uv-Vis spectrophotometer. The results were obtained with concentrations of total phenolic of 5,47%, total flavonoid of 1,92%, and the total carotenoid of 0, 044%.